Dicentrine: The Major Alkaloid of Cyclea laxiflara Miers - Lajis, Md Nordin; Samadi, Zainuddin; Ismail, Norhayati (1991)
The major alkaloid of Cyclea laxiflora Miers. was isolated and identified as dicentrine from its spectral and physical data.